2013
DOI: 10.1002/anie.201302090
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin PtPdTe Nanowires as Superior Catalysts for Methanol Electrooxidation

Abstract: Ultrathin and ultralong: Highly uniform, ultrathin (diameter 5-7 nm), and ultralong (aspect ratio >10(4)) PtPdTe nanowires (NWs) were synthesized by using a facile method employing Te NWs as both sacrificial templates and reducing agents. Fine-tuning of the molar ratios of Pt and Pd precursors afforded PtPdTe NWs with different compositions and enhanced electroactivity in the methanol oxidation reaction in comparison with a commercial Pt/C catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(97 citation statements)
references
References 52 publications
5
91
1
Order By: Relevance
“…However, compared with Pt standard atlas, the peaks values of Pt 4f 5/2 and Pt 4f 7/2 were less 0.034 eV and 0.1 eV than them of Pt 0 respectively. The consequence might be caused by valency unsaturated atoms in edges and corners 11,12,28,29 . As seen in Figure 1, the TEM images of Pt nano-flowers under different magnifications showed an interesting structure with a remarkable distribution in size and shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with Pt standard atlas, the peaks values of Pt 4f 5/2 and Pt 4f 7/2 were less 0.034 eV and 0.1 eV than them of Pt 0 respectively. The consequence might be caused by valency unsaturated atoms in edges and corners 11,12,28,29 . As seen in Figure 1, the TEM images of Pt nano-flowers under different magnifications showed an interesting structure with a remarkable distribution in size and shape.…”
Section: Resultsmentioning
confidence: 99%
“…The core level of Pt 4f split into 4f 5/2 and 4f 7/2 states because of spin-orbital splitting 28,29 . The results of binding .…”
Section: Resultsmentioning
confidence: 99%
“…Among these methods, the introduction of other metals (e.g., Pd, Au, Ag, Fe, Ni, Cu) into Pt to form Pt based alloys or composites not only reduces the overall Pt consumption, but also enhances the electrocatalytic activity of Pt catalysts [11,12]. For example, Yu et al synthesized ultrathin PtPdTe nanowires with enhanced activity toward MOR [13]. Zhang et al reported that PteCu alloy concave nanocubes with high-index facets exhibited substantially enhanced activity for MOR [14].…”
Section: Introductionmentioning
confidence: 98%
“…For comparison, AuPtCu/C, PtCu/C and commercial Pt/C electrocatalysts were also examined. Since pure Au and Cu catalyst was not active for methanol oxidation reaction, and the addition of Au and Cu can enhance catalytic activity of Pt, the catalyst activity was evaluated in the base of Pt [30,31]. CV curves in Fig.…”
Section: Resultsmentioning
confidence: 99%